Characterization of the white ovals on Jupiter's southern hemisphere using the first data by the Juno/JIRAM instrument. Issue 10 (25th May 2017) - Sindoni, G.; Grassi, D.; Adriani, A.; Mura, A.; Moriconi, M. L.; Dinelli, B. M.; Filacchione, G.; Tosi, F.; Piccioni, G.; Migliorini, A.; Altieri, F.; Fabiano, F.; et al.
Abstract: During the first perijove passage of the Juno mission, the Jovian InfraRed Auroral Mapper (JIRAM) observed a line of closely spaced oval features in Jupiter's southern hemisphere, between 30°S and 45°S. In this work, we focused on the longitudinal region covering the three ovals having higher contrast at 5 μm, i.e., between 120°W and 60°W in System III coordinates. We used the JIRAM's full spectral capability in the range 2.4–3 μm together with a Bayesian data inversion approach to retrieve maps of column densities and altitudes for an NH3 cloud and an N2 H4 haze. The deep (under the saturation level) volume mixing ratio and the relative humidity for gaseous ammonia were also retrieved. Our results suggest different vortex activity for the three ovals. Updraft and downdraft together with considerations about the ammonia condensation could explain our maps providing evidences of cyclonic and anticyclonic structures. Key Points: JIRAM data from first Juno orbit highlighted the presence of several ovals in Jupiter's southern hemisphere Column densities and altitudes for an NH3 cloud and an N2 H4 haze have been retrieved for three ovals in the region between 60–120°W and 30–45°S Evidences of cyclonic and anticyclonic structures inside the ovals have been found